Dynamics of a Complex Spatially Distributed Hutchinson Equation - D. S. Glyzin; S. A. Kaschenko (Моделирование и анализ информационных систем)
In the article the complex Hutchinson equation is studied. New results on numerically observable space-inhomogenious solutions are obtained.